Team Emotional Intelligence: Emotional Processes as a Link Between Managers and Workers - Mindeguia, Rosa; Aritzeta, Aitor; Garmendia, Alaine; Martinez-Moreno, Edurne; Elorza, Unai; Soroa, Goretti (Frontiers in Psychology, 2021)
Research has shown that transformational leaders are able, through emotional contagion mechanisms, to transmit their emotions and boost positive feelings among their followers. Although research on leadership and team processes have shown a positive relation between transformational leadership and performance, there is a lack of studies examining the “black box” of this association. The present study aimed to assess the mediation effect of team emotional intelligence (TEI) of the management team on the relationship between management’s transformational behaviors and employees’ responses. Data were gathered from two sources: 1,566 managers grouped into 188 teams pertaining to a total of 90 firms, and 4,564 workers from the same 90 firms. The results showed that management team TEI and the emotional state of ‘passion’ among employees had a full mediation effect on the relationship between management teams’ transformational leadership and employees’ cohesion. Implications of these results are discussed.